2014
DOI: 10.1007/s12639-014-0635-z
|View full text |Cite
|
Sign up to set email alerts
|

Immune response of newborn BALB/c mice to Cryptosporidium infection

Abstract: Cryptosporidium parvum is a protozoan parasite which causes diarrheal in human and animals worldwide. Infection transmission has reported through oralfecal by infectious objects through foods and drinks. In this study we explored the immune response pathway in animal model for C. parvum to develop the new treatment way. Oocysts collected from fecal positive for C. parvum and diluted about 1:5 in sucrose solution. New born BALB/c mice (3 days) divided to 2 different groups. Control group hadn't received any ooc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In studies about hepatitis B immunization, it is reported that different age groups of BALB/c mice were included such as age of 4-6 weeks (Granovski et al, 2017; et al, 2017), 6-8 weeks (Gui et al, 2017;Kapadia et al, 2017;Skrastina et al, 2014;Fakharzadeh et al, 2013), 8-10 weeks (McCluskie et al, 2002Abdalla et al, 2014), 11 weeks (Perez et al, 2018), or 1,3,7 days (Weeratna et al, 2001;Ahmadian et al, 2016), among which ages of 6-8 weeks were in the majority. So it is suggested that mice of a certain age group can be selected as flexible according to different experimental requirements.…”
Section: Discussionmentioning
confidence: 99%
“…In studies about hepatitis B immunization, it is reported that different age groups of BALB/c mice were included such as age of 4-6 weeks (Granovski et al, 2017; et al, 2017), 6-8 weeks (Gui et al, 2017;Kapadia et al, 2017;Skrastina et al, 2014;Fakharzadeh et al, 2013), 8-10 weeks (McCluskie et al, 2002Abdalla et al, 2014), 11 weeks (Perez et al, 2018), or 1,3,7 days (Weeratna et al, 2001;Ahmadian et al, 2016), among which ages of 6-8 weeks were in the majority. So it is suggested that mice of a certain age group can be selected as flexible according to different experimental requirements.…”
Section: Discussionmentioning
confidence: 99%